Identification of core genes as potential biomarkers for predicting progression and prognosis in glioblastoma - Zeng, Jianping; Hua, Shushan; Liu, Jing; Mungur, Rajneesh; He, Yongsheng; Feng, Jiugeng (Frontiers in Genetics, 2022)
Background: Glioblastoma is a common malignant neuroepithelial neoplasm with poor clinical outcome and limited treatment options. It is extremely important to search and confirm diverse hub genes that are effective in the advance and prediction of glioblastoma. Methods: We analyzed three microarray datasets (GSE50161, GSE4290, GSE68848), which was derived from the GEO database. GO function and KEGG pathway enrichment analysis for Differentially Expressed Genes (DEGs) were performed using the DAVID. PPI network of these DEGs was analyzed based on the Search Tool for the Retrieval of Interacting Genes database and visualized by Cytoscape software. Hub genes were identified through PPI network and Robust Rank Aggregation method. The Cancer Genome Atlas (TCGA) and Oncomine database were used to perform the validation of hub genes. In addition, the survival curve analysis was also conducted to verify the correlation between the expression of hub genes and prognosis. The human glioblastoma cells and normal cells were collected and then RT-PCR, Western-blot and immunofluorescence were conducted to validate the expression of NDC80. A Cell Counting Kit-8 (CCK-8) assay were used to detect the proliferative of glioma cells. The effects of NDC80 on migration and invasion of GBM cell lines were evaluated by conducting scratch assay and transwell assay. Results: A total of 716 overlapping genes were in the common region, containing 188 upregulated DEGs and 528 downregulated DEGs. The expression of ten hub genes in TCGA and Oncomine database were significantly overexpressed in glioblastoma compared with normal ones. Besides, the survival analysis showed that the patients with low expression of six genes (BIR5C, CDC20, NDC80, CDK1, TOP2A and MELK) had a significant favorable prognosis (P < 0.01). The RT-PCR, western blot and immunofluorescence results showed that the expression level of NDC80 was significantly higher in human glioblastoma cells than in normal cells. Moreover, we identified that NDC80 up-regulates the proliferation and invasion abilities of human glioblastoma cells. Conclusions: The distinguished six genes may be utilized to form a board of progressive and predictive biomarkers of glioblastoma for clinical purpose. Especially, NDC80 was discovered that may play an important role in glioblastoma.